Heterogeneous salinity in the root system of bell pepper in greenhouse - Oliveira, Francisco de A. de; Alves, Rita de C. [UNESP]; Bezerra, Francisco M. S.; Lima, Luan A.; Medeiros, Ana S. de; Silva, Nicolly K. C. (Univ Federal Campina Grande, 2018)
The split-root technique was used as a strategy to reduce saline stress on pepper. A completely randomized design with six treatments and four replicates was used. The treatments consisted of six saline water application strategies (T1 - salinized nutrient solution (S1 = 1.4 dS m(-1)) during the whole cycle; T2 - salinized nutrient solution (S2 = 4.5 dS m(-1)) throughout the cycle, T3 - S1 and S2 throughout the cycle, using two emitters and without splitting the root system, T4 - S1 and S2, using two emitters and splitting the root system by a plastic film, T5 - S1 and S2, using two emitters and splitting the root system, alternating the solutions every 15 days, T6 - S1 and S2, using two emitters and with out splitting the root system, alternating the solutions every 15 days). Five fruit harvests were performed, and the plants were harvested at 85 days after initiation of treatments and evaluated for the following variables: leaf number, leaf area, plant height, stem diameter, shoot dry matter (stem + leaves + fruits), root dry matter, number of fruits, fresh fruit weight and fruit production per plant. Most of the variables were reduced by the salinity of irrigation water. The highest fruit yields were obtained using low-salinity water, with the mixture of non-saline and saline waters, and alternating biweekly when the root system was split, demonstrating the viability of these three techniques.
Keywords: Capsicum annuum L.; saline water; fertigation